Treatment of cystic ovarian disease with Naloxone in high production dairy cows - Palomar, Martín Manuel (2008)
Cystic ovarian disease (COD) is an important cause of abnormal oestrous behaviour and infertility in dairy cows. Ovarian cysts are defined as follicle-like structures of diameter >25 mm persisting for at least 10 days in the absence of a corpus luteum (Garverick, 1997). The prevalence of COD in dairy herds has been reported to vary from 5% to 30% (Vanholder et al., 2006) and this condition may result in significant economic losses to the dairy industry because of increased calving to conception and inter-calving intervals (Peter, 2004).